Ethics of Intercultural Communication among Ethnic Chinese in Kampung Kapitan Palembang - Henny Yusalia (Jurnal Studi Sosial dan Politik, 2024)
This research aims to know and understand the forms of communication ethics that take place in different cultural communities in Kampung Kapitan Palembang, especially the Chinese community with local residents. That are causes the relationship between ethnic Chinese descendants is often problematic and often considered not to blend in with local residents. Methodologically, this research uses a qualitative approach and practically uses Hymes' ethnography of communication. The researcher observed communication events in Kapitan Village for about 3 months, and interviewed 5 resource persons. The researcher also collected a variety of relevant literature materials. Furthermore, the data was analyzed using qualitative interactive analysis. The results showed that there are five forms of communication ethics that develop in Kapitan Village, namely the use of special designations for calls, the term “wong Cino wong kito”, the existence of low and high context communication, the prohibition of fighting on holidays, and adherence to tradition. This communication ethic is built on historical aspects and sociocultural conditions in the community. This ethic is able to build harmony even though differences in ethnic identity still appear.